Review of technology trends in new space missions using a patent analytics approach - Garzaniti, Nicola; Tekic, Zeljko; Kukolj, Dragan; Golkar, Alessandro (Progress in aerospace sciences, 2021)
This review paper analyzes technology trends observed in New Space missions, using a patent analytics approach. The analysis is complemented with a literature review of the subjects identified. The main objective of this review is to draw a comprehensive picture of technology trends in New Space and to discuss potential scenarios for further development of this novel type of missions. Building on the existing scientific literature, we survey alternative definitions and then propose our own definition of New Space missions as synthesis of the ongoing debate in the field. We identified more than two hundred organizations active in the development of both upstream and downstream products and services for New Space missions. Using a commercially available patent analytics tool, we collected 933 patents protecting technologies disclosed by those organizations. We used the Latent Dirichlet Allocation (LDA), a topic modeling algorithm, to analyze patents' data and to identify the underlying structures in New Space's technology trends. Ten major topics have been identified respectively named “Remote sensing & image acquisition”, “Flying/launch systems”, “Telecommunication systems”, “Constellation management”, “Digital Processing Architectures”, “Image analysis”, “Manufacturing process & materials”, “Feature recognition and extraction”, “Antenna systems”, and “Space platforms”. A deeper analysis of patents' claims revealed a core cluster defined as “data cluster” including data analysis topics (Remote sensing & image acquisition, Image analysis, and Feature recognition and extraction), data transmission topics (Telecommunication systems and Antenna systems from both hardware and software perspective) and related enabling technologies such as constellation management. Based on this analysis, the evolution of data cluster related technologies is surveyed in order to review the current technology state of the art as well as identifying potential areas that will benefit the most from further technology developments to improve New Space missions’ performance. Lastly, we identify technology trends for future New Space development based on the insights obtained by the synthesis of our literature and patent survey. We discuss the key directions for future development emerging from our review, such as the use of commercial off the shelf components, the increasing use of miniaturized technology, and software defined technology.